Implementasi Eoip Tunnel Dan Bonding Di Routerboad Mikrotik Untuk Menambah Kapasitas Wireless Link Di Pt Gomeds Network - Dedi Setiawan; Andi Bode; Warid Yunus (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
Information technology in the world has been experiencing rapid development, and Indonesia is no exception. In Indonesia, internet access is increasingly widespread in remote villages provided by ISPs. Precisely on the island of Sulawesi, there are several ISPs, one of which is PT Gomeds Network. PT Gomeds Network is a company engaged in internet network provider services. It was founded on January 17, 2011, in Gorontalo. It has infrastructure spread throughout the island of Sulawesi. PT Gomeds Network utilizes wireless network technology. Each Base Transceiver Station (BTS) has a different local link capacity. The problem experienced by PT Gomeds Network is the insufficient capacity of the BTS wireless link and the absence of a backup Wireless Link at each BTS when the Wireless Radio device or the main link line connecting the BTS is lost or damaged. The purpose of this study is to increase the wireless link capacity of BTS so that customers connected to BTS can receive services based on the internet package rented and provide benefits in the form of a backup wireless link when one of the wireless link lines is down due to damage. The results of this study explain that the EOIP Tunnel and Bonding methods can run as expected and produce adequate BTS capacity, and backup wireless links for BTS can function without disconnecting wireless links.